2010
DOI: 10.1016/j.seizure.2010.05.004
|View full text |Cite
|
Sign up to set email alerts
|

ABCB1 C3435T polymorphism and the risk of resistance to antiepileptic drugs in epilepsy: A systematic review and meta-analysis

Abstract: We failed to show an association between the ABCB1 C3435T polymorphism and the risk of drug-resistance suggesting a revision in contribution of this polymorphism in the multi-drug transporters hypothesis of pharmacoresistance to AEDs in epilepsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
56
4
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(71 citation statements)
references
References 44 publications
5
56
4
4
Order By: Relevance
“…Several recent meta analyses of studies investigating the c.3435C>T polymorphism are listed in table 3. Digoxin pharmacokinetics were not affected by c.3435C>T [98] and the response to anticonvulsant drugs exhibited also no association with this polymorphism [99,100]. In contrast, the effects on cyclosporine pharmacokinetics are more complex: Overall, there was no effect of the c.3435C>T ABCB1 polymorphism on the pharmacokinetic parameters, although the total cyclosporine bioavailability (AUC 0-12 ) was slightly reduced (table 3) [101].…”
Section: Mdr1 (Abcb1)mentioning
confidence: 95%
“…Several recent meta analyses of studies investigating the c.3435C>T polymorphism are listed in table 3. Digoxin pharmacokinetics were not affected by c.3435C>T [98] and the response to anticonvulsant drugs exhibited also no association with this polymorphism [99,100]. In contrast, the effects on cyclosporine pharmacokinetics are more complex: Overall, there was no effect of the c.3435C>T ABCB1 polymorphism on the pharmacokinetic parameters, although the total cyclosporine bioavailability (AUC 0-12 ) was slightly reduced (table 3) [101].…”
Section: Mdr1 (Abcb1)mentioning
confidence: 95%
“…Epilepsy patients with the CC genotype had lower levels of phenobarbital in the CSF and exhibited higher seizure activity [72]. The first study, in 2003, suggested that the 3435C > T polymorphism may explain resistance to AED therapy in epilepsy [73], but several other association studies, as well as meta-analyses, have clearly demonstrated that the impact of ABCB1 genetics on the pharmacoresistance of AEDs is inconsistent [62,74,75]. However, the concept that Pgp expression and function may be directly associated with pharmacoresistant temporal lobe epilepsy in patients has been very recently corroborated by a highly attractive approach investigating Pgp activity in patients with epilepsy using positron emission tomography technology [76].…”
Section: Role Of Drug Distribution For Pharmacoresponsementioning
confidence: 99%
“…Atorvastatin (Keskitalo et al, 2008) Carboplatin (Hamidovic et al, 2010) Digoxin (Johne et al, 2002) Docetaxel (Sissung et al, 2008) Fluvastatin, Pravastatin, Lovastatin, and Rosuvastatin, no effect (Keskitalo et al, 2009a) Paclitaxel (Sissung et al, 2006;Chang et al, 2010;Hamidovic et al, 2010) Simvastatin acid (Keskitalo et al, 2008) Various antiepileptic drugs (Sisodiya and Goldstein, 2007;Seo et al, 2008;Kwan et al, 2009;Haerian et al, 2010;Nurmohamed et al, 2010) Cisplatin (Filipski et al, 2009) Imatinib (White et al, 2007(White et al, , 2010a(White et al, , 2010bEngler et al, 2010) Metformin (Shu et al, 2007(Shu et al, , 2008Tzvetkov et al, 2009) …”
Section: Reduced Therapeutic Effectmentioning
confidence: 99%